Doyle, New men, new cities, new South - Atlanta, Nashville, Charleston, Mobile, 1860-1910 - Billington, Monroe (Teaching History: A Journal of Methods, 1991)
The New Men in the title of this volume include a variety of people who led the South after the Civil War, but the important ones were middle-aged businessmen who had lived in the South before the Civil War and who were less than enthusiastic about the formation and activities of the southern Confederacy. This would not today be considered a revisionist view, but it certainly does not comply with older interpretations of these leaders.